Effectiveness of Teamwork Excellence Training: A Case Study at PT ICI Manado - Djuuna, Meykel; Danang, Surya; Jusuf, Sabrun (Journal of Management and Administration Provision, 2025)
This study aims to improve team performance at PT. Insan Cerdas Indonesia (ICI), Ranotana Branch, through a psychological intervention in the form of the "Teamwork Excellence" training program. The research began with an assessment that identified psychological dysfunctions within the team, such as ineffective communication, unclear role division, and low psychological safety. The methodology employed was a combination of qualitative and quantitative approaches, including observation, structured interviews with the HR Manager and Branch Head, as well as psychological assessments using the Training Needs Analysis (TNA) and Team Climate Inventory (TCI). The intervention was conducted with seven staff members through a one-day experiential training. The results showed significant improvements in vision clarity, participative safety, task orientation, and support for innovation. Participants’ average posttest scores increased by 18.57% compared to the pretest. Qualitative findings also indicated enhanced initiative, openness in communication, and team cohesion after the intervention. The study concludes that well targeted psychological interventions can effectively enhance team dynamics. It is recommended that the organization continue sustainable development programs to maintain and further improve team performance.